Chemometric Discrimination of Different Tomato Cultivars Based on Their Volatile Fingerprint in Relation to Lycopene and Total Phenolics Content. Issue 2 (21st November 2013) - Socaci, Sonia A.; Socaciu, Carmen; Mureşan, Crina; Fărcaş, Anca; Tofană, Maria; Vicaş, Simona; Pintea, Adela
ABSTRACT Introduction The characteristic flavour of tomato is given by a complex mixture of sugars, acids, amino acids, minerals and volatile metabolites. Of these, volatile compounds are considered to greatly influence the flavour of tomato fruits. The volatile aroma compounds and phytochemical content of tomatoes are dependent on genotype, environmental conditions and cultural practices, and can thus be used for cultivar discrimination. Objective To assess the possibility of using the volatile profile of tomato to fingerprint and discriminate different tomato cultivars based on an 'in‐tube extraction' technique coupled to gas chromatography, combined with mass spectrometry (ITEX/GC–MS) and a chemometric approach. Results Using the ITEX/GC–MS technique, 61 volatiles were analysed and separated from tomato cultivars, with 58 being identified. The main volatiles identified in all tomato cultivars were: hexanal, trans‐2‐hexenal, 1‐hexanol, 3‐pentanone, 3‐methylbutanol, 2‐methylbutanol, 3‐methylbutanal and 6‐methyl‐5‐hepten‐2‐one. The lycopene content and total phenolic compound content of the tomato cultivars varied between 36.78 and 73.18 mg/kg fresh weight (fw) and from 119.4 to 253.7 mg of gallic acid equivalents (GAE) per kilogram fresh weight, respectively. Volatile fingerprint and phytochemical composition led to a good differentiation between tomato cultivars, with the first two principal components explaining 89% of the variance in the data. Conclusion The tomato cultivars studied were easily discriminated based on their characteristic volatile profile that was obtained using the reliable ITEX/GC–MS technique. Principal component analysis revealed, in addition to volatile compounds, the important role played by the total phenolic content in tomato cultivar discrimination, which is highly correlated with phenotypic and biochemical differences between tomato cultivars. Copyright © 2013 John Wiley & Sons, Ltd.